2021
DOI: 10.1038/s41598-021-03170-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome association study for DNA methylation biomarkers in buccal and monocyte cells for female rheumatoid arthritis

Abstract: Genetics (i.e., mutations) has been assumed to be the major factor in rheumatoid arthritis (RA) etiology, but accounts for a minority of the variance in disease risk for RA. In contrast to genetics, the environment can have dramatic impacts on epigenetics that associate with disease etiology. The current study used buccal cells and purified blood monocytes from two different clinical cohorts involving Caucasian or African American female populations with or without arthritis. The differential DNA methylation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…This occurred even though cheek buccal cells are not directly involved in gestation, which suggests surrogate marker cell samples can be useful to detect epigenetic biomarkers of disease. This is supported by a recent study that used buccal cells to identify epigenetic biomarkers for female rheumatoid arthritis 46 .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This occurred even though cheek buccal cells are not directly involved in gestation, which suggests surrogate marker cell samples can be useful to detect epigenetic biomarkers of disease. This is supported by a recent study that used buccal cells to identify epigenetic biomarkers for female rheumatoid arthritis 46 .…”
Section: Discussionmentioning
confidence: 52%
“…Previously, it has been shown that DNA methylation at the SLC9B1 gene in blood samples from pregnant women between 24 and 32 weeks gestation can predict whether the fetus is at risk for fetal intolerance of labor, which can cause fetal hypoxia, and is an indication for performing a Caesarean section 45 . In a recent study, we have used buccal cells as an easily obtained purified cell population to identify epigenetic (i.e., DNA methylation) biomarkers for female rheumatoid arthritis 46 . Although sperm epigenetic biomarkers reflect epigenetic inheritance of disease in offspring and subsequent generations, a surrogate cell such as buccal cells can reflect early embryo impacts on all somatic cells to be used for disease assessment 46 , 47 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The buccal cells were used as a marker cell for alterations in epigenetics for each individual. Similar analyses have been performed for disease specific comparisons, such as female susceptibility for arthritis [24][25][26][27][28] . The DNA was isolated from the buccal cells and used in a methylated DNA immunoprecipitation (MeDIP) protocol followed by next generation sequencing (MeDIP-Seq), as described in the Methods 24 .…”
Section: Resultsmentioning
confidence: 96%
“…Researchers from Washington State University (WSU) and Arthritis Northwest in Spokane, Washington, identified a set of epimutations in cells from women who had rheumatoid arthritis (RA) that were distinct from those without the joint-damaging autoimmune disease. (See Craig et al, 2021. ) Epimutations are molecular factors and processes around DNA that regulate genome activity, independent of DNA sequence.…”
Section: Referencesmentioning
confidence: 99%